Factors affecting intended hospitable behaviour to tourists: hosting Chinese tourists in a post-Covid-19 world. Issue 2 (3rd April 2021) - Armutlu, Mansur Emre; Bakır, Ahmet Can; Sönmez, Hande; Zorer, Esra; Alvarez, Maria D.
ABSTRACT: Since the Covid-19 virus appeared the resulting pandemic has been associated with China and the Chinese in the media. This research, using the Integrated Threat Theory's perspective, aims to understand the effect that this association may have on host-guest relations. The study, based on 537 questionnaires collected online, investigates whether the hospitable behaviour to be shown by the Turkish hosts to Chinese tourists in the aftermath of the Covid-19 pandemic is influenced by risk perceptions, and by views of the Chinese and their responsibility in the spread of the virus. The findings confirm the strong negative influence of perceived risk of infection, the weaker positive effect of perceptions of the Chinese, and the indirect impact of attribution of responsibility.